2014
DOI: 10.14295/bds.2014.v17i3.1003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crosshead speed influence on shear bond strength test

Abstract: <p><span style="font-size: medium;">The objective of this study was to evaluate the influence of different speeds using the piston device in the shear bond strength. 48 cylinders of composed resin had been confectioned (Solidex),and were divided randomly in four groups (n=12).</span><span style="font-size: medium;">  </span><span style="font-size: medium;">The specimens were adapted to the device for the</span><span style="font-size: medium;">  </span><s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Aging of the material under laboratory in-vitro condition was fulfilled through thermocycling to simulate the stresses to which teeth and the sealants are subjected to in the oral environment. Thermocycling generates repeated cycles of expansion and contractions at the interface between the enamel and the resin material and this is because of the high expansion contraction coefficient of the resin material (25,30,37). All specimen were directed perpendicularly centralized over enamel surface so as the buccal surface of each tooth was parallel to the mold, as it allows the direction of shearing force to be perpendicular to the bonded specimen, sealants were applied and cured according to the manufacturer's instructions material all specimens were subjected to shear force in universal testing machine so as the shearing rod will be perpendicular to the specimens (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Aging of the material under laboratory in-vitro condition was fulfilled through thermocycling to simulate the stresses to which teeth and the sealants are subjected to in the oral environment. Thermocycling generates repeated cycles of expansion and contractions at the interface between the enamel and the resin material and this is because of the high expansion contraction coefficient of the resin material (25,30,37). All specimen were directed perpendicularly centralized over enamel surface so as the buccal surface of each tooth was parallel to the mold, as it allows the direction of shearing force to be perpendicular to the bonded specimen, sealants were applied and cured according to the manufacturer's instructions material all specimens were subjected to shear force in universal testing machine so as the shearing rod will be perpendicular to the specimens (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Therewith, the crosshead speed seems to have an influence on the shear bond strength. Literature reports speed values ranging between 0.5 and 2.0 mm/min [ 28 ]. However, an ISO guideline (TR 11405) recommends applying a crosshead speed between 0.45 and 1.05 mm/min (International Organization for Standardization, ISO TR 11405: Guidance on testing of adhesion in tooth structure, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Some research shows that the crosshead speed influences the results of the SBS tests, other does not confirm that. 18,19 In the previous research on the changes in the bond strength of composite to MTA, depending on the time of composite placement, it was suggested that changes in the porosity of MTA during its setting may have an impact on the bond strength. Initially, the MTA is more porous so there are more microretentions available for the adhesive system.…”
Section: Discussionmentioning
confidence: 99%